THE EFFECT OF DIFFERENT BINDING MATERIALS ON THE QUALITY OFSMOKE FLAVORED CATFISH (Pangasius hypophthalmus) NUGGET DURING STORAGE AT COLD TEMPERATURE (5 ± 2ºC) - Roy Saputra Situmorang; N. Ira Sari; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis study was aimed to determine the effect of different binding materials added on the quality of on the quality of smoke flavored catfish (Pangasius hypophthalmus) nugget during storage at cold temperature (5 ± 2 ºc). The method used was an experimental method. The research was designed for a Randomized Completely Blocked Design (RCBD). The treatment factor was consisting of 3 kinds of binding materials, namely the addition of tapioca flour (Ta), wheat flour (Te), sago flour (Sa). As a block was the storage time of the smoked flavor catfish nugget at cold temperature (5 ± 2 ºC) for 0 day (as a control treatment), 7 days, and 14 days. The parameters observed were total bacteria plate count (TPC), the growth of Staphylococcus aureus bacteria, pH value, water content, and sensory evaluation (appearance, smell, taste and texture). The results showed that the wheat flour was the best binding material, indicated by the total bacteria plate count of 4.3 x 104Cfu / g, Staphylococcus aureus was counted 7.5 x 102 Cfu/ g), pH value 4.8, water content 30.1%, and the value of sensory evaluation were appearance at 5.0, odor at 4.7, taste at 5.2, and texture at 5.1 during storage for 14days at cold temperature (5 ± 2 ºC).  Keywords: Binding,catfish nugget,cold storage, quality.